Residents' resilience towards insecurity in Maiduguri, Borno State, Nigeria - Butu, Hauwa Mai; Hashim, Ahmad Hariza; Ahmad, Nobaya (Universiti Putra Malaysia Press, 2019)
It is obvious that the demand for security is one of the basic needs for human survival, and the effects of terrorist such as Boko Haram on the society have gone beyond the expectations of individuals in Maiduguri, Borno State Nigeria. Even though many have relocated themselves out of the area, there are still those who continued to stay in the neighborhood. Therefore, the general objective of this paper is to examine the level of residents' resilience and to compare if there are significant differences in the level of resilience based on age, gender and religious inclination towards insecurity in Maiduguri. Resilience Theory by Kurt Lewin (1943) was used to underpin this study. Using a structured questionnaire, data were collected from a total of 383 respondents in Maiduguri. The findings from the descriptive statistics revealed a moderate level of resilience among the residents (M = 3.09, SD =0.78). Independent sample t-test showed a statistically significant difference in the level of resilience between male and females (t (381) = -2.518, p < 0.05). Additionally the ANOVA analysis revealed no significant difference in the level of resilience based on age and religious inclination (F (2,380) = 1.105, p >0.05 and F (2,380) = 0.771, p > 0.05). Based on the findings, the authors concluded that females were found to revitalize more easily as compared to males after an attack. In general, there are some residents in the study area who show the ability to revitalize and withstand the security threat and resist relocation irrespective of their age and religious inclination. Thus, the authors are of the opinion that to ensure safe neighbourhood, the government should not only concentrate on the rehabilitation of internally displaced person but efforts should also be geared towards the residents who decided to remain in the neighbourhood even though it is affected by the insurgency.